Immunomodulator Effect of Lemongrass Extract (Cymbopogon nardus L.) to Increase Immune Cells as a Precaution Against SARS-CoV-2 - Setiyowati, Putri Ayu Ika; Solekha, Rofiatun; Negara, Sri Bintang Sahara Mahaputra Kusuma; Rosalina, Reny (Biomolecular and Health Science Journal, 2021)
Introduction: In humans, Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) can damage some tissue when the immune systems was decrease. Natural product from the plant often used to improve immune response against microorganism including virus. This study aimed to determine the potential antioxidant of lemongrass extract (C . nardus) with various dosage that can provide immunomodulatory effects and find an optimal dosage to be used. Methods: The method used observasional analytic, using animal model of 30 male mice strain BALB/C, weight 25-30 gram, divided into 5 groups; the positive control group was given 0.05 mL of 0.05% CMC within 14 days, negative control group was given IMBOOST® tablet 200 mg/kg body weight (bw) within 14 days, treatment groups were given C. nardus extract with various doses 50 mg/kg bw, 150 mg/kg bw, and 300 mg/kg bw. In day 21 all group were injected with 0,2 ml of pathogen bacterial (S. aureus). Blood samples were taken three times: 7th day, 14th day, and 21th day. Results: The results showed that lemongrass extract (C. nardus) was able to influence the leukocyte and lymphocytes count with significant different (p<0.05). The optimal dose is 150 mg/kg body weight. Conclusion: The antioxidant compounds that contain in the C. nardus extract have an ability to increasing the immune system in the dose 150 mg/kg bw , but in the dose 300 mg/kg bw became toxic that can make a skin injury or death in animal test.